Performance Improvement Analysis of Design and Build Construction Project Managers of State Builidngs - Jujuk Kusumawati (Universitas Dharma Wacana, 2025)
Project managers of planning and construction of government buildings are experts of the implementing contractor who determine the timeliness of the implementation of design and build construction. In order for timely implementation, project managers not only have higher education and long experience, but must have a good work culture and work behavior as well. Therefore, it is necessary to examine project performance based on the work performance of project managers